Studi Kualitatif Penerapan Model Komunikasi Terapeutik Berbasis Hildegard E Peplau Teori Pada Mutu Pelayanan Keperawatan Gawat Darurat - Gunawan Gunawan; Blacius Dedi; Tri Ismu Pujianto; Ali Muhlasin (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2026)
Nursing services in the Emergency Department (ED) require fast and accurate actions, demanding effective communication amid high work pressure. This study aimed to explore nurses’ experiences, identify ideas, challenges, and suggestions in implementing a therapeutic communication model based on Hildegard E. Peplau’s theory, and examine its impact on the quality of nursing services in the ED of RSUD dr. Loekmonohadi Kudus. This qualitative study employed an Action Research design and involved eight ED nurses selected through purposive sampling. Data were collected using a Focus Group Discussion (FGD) module and were analyzed through thematic analysis, following workshops and expert consultations. The results indicated that nurses maintained effective communication despite high mobility demands by strategically tailoring their approach to patient conditions, fostering trust, and integrating holistic nursing care principles. Communication effectiveness was further strengthened through soft skills training and leadership support. The study recommends ongoing training, the development of standardized communication modules, and systemic support to reinforce therapeutic communication practices. These findings contribute to advancing humanistic and patient-centered nursing practices in high-acuity emergency care settings.